Fortification of rapoko (Eleusine coracana L) and cowpeas (Vigna unguiculata) for improved macro and micro nutritents among children below the age of 5 years - Chinyama, John (BUSE, 2020)
This study aimed at developing a fortified Rapoko-Cowpea porridge blend named (RaCoB) and evaluate its acceptability to enhance macro and micronutrients intake among children below the age of 5 years. Rapoko proximate and mineral composition results were used as a control during blend formulation. Results of this research were compared to other studies and their ability to meet WHO daily nutrients requirements for children under the age of 5 years as a control mechanism. A Completely Randomised Design (CRD) was used with three treatments (blends) replicated three times. A mixed method research approach was adopted which consisted of an experiment (quantitative) for proximate analysis of rapoko, cowpeas and RaCoB ingredients. Sensory evaluation was done with 100 panelists to establish the overall acceptability of the blends. Vendors at Mbare market were categorized into three clusters based on where they source rapoko and cowpea grains (Masvingo, Murewa, Gokwe) as a way of managing uncontrolled variation. Simple random sampling was used to select three vendors where equal amounts of rapoko, and cowpea grains were bought and constituted to make 5 kg. Proximate analysis was done using standard AOAC methods for cow pea, rapoko and all the three formulated blends (RaCoB1; RaCoB2 and RaCoB3). The results of the proximate analysis showed that the mean difference in rapoko and cowpea elements is significant at 5% level. There is statistical significance difference in the proximate composition of the RaCoB blends at p<0.05. Blend ratio rapoko: cowpeas (75:25) had the highest carbohydrates, protein, zinc, iron, energy, and vitamins with blend (85:15) having the lowest. Sensory evaluation results from the three blends showed that blend ratio (75:25) was the most preferred blend. Women who normally feed porridge to children and have better olfactory blub necessary in determining sensory attributes than men also preferred the same blend. In conclusion the results have proved that rapoko, cowpeas and RaCoB blends have high macro and micronutrients to support daily nutritional requirements of children below the age of 5 years. Further studies are required to establish the effects of anti-nutritional factors, bioavailability, shelf life and commercialization of RaCoB blend. The government is therefore encouraged to invest more in nutrition and address inequalities in food, health systems. It may deliberately develop a policy that promotes fortification of cereals and pulses. Strengthening of the rapoko and cowpea value chain is required in terms at both input and output level. Key words: Malnutrition, Fortification, Macro nutrients, Micronutrients, Cowpeas, Rapoko, Sensory evaluation,
Keywords: Malnutrition; Fortified food; Cowpeas; Rapoko